2014
DOI: 10.4236/fmar.2014.23013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Lead Hepatotoxicity; Histological, Histochemical and Ultrastructural Study

Abstract: Lead is one of the most well-known naturally occurring environmental heavy metals. This experimental study was designed to evaluate lead induced toxic effects on hepatocytes and lobular architecture as judged microscopically. Material and Methods: This study was conducted in anatomy department, Benha faculty of medicine, Benha University, Egypt from May to October 2013 on 30 normal adult albino rats divided into 3 groups; one control and 2 experimental groups. The experimental groups were given 0.13% lead acet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 14 publications
0
12
0
1
Order By: Relevance
“…Lead also causes oxidative cellular and tissue damage to the liver . In animal models, there is an association between hepatotoxicity and blood lead levels …”
Section: Introductionmentioning
confidence: 99%
“…Lead also causes oxidative cellular and tissue damage to the liver . In animal models, there is an association between hepatotoxicity and blood lead levels …”
Section: Introductionmentioning
confidence: 99%
“…We hypothesized that sustained lead exposure contributed to chronic inflammation which predisposed hepatic fibrosis. Histopathological findings from animal experiments 23,24 and two human case reports of acute lead poisoning with unexplained hepatitis demonstrated extensive microvesicular and macrovesicular steatosis, portal and intralobular lymphocytic infiltrate, disrupt liver parenchymal architecture and pericellular fibrosis 11,23 . Our study used LS as a non-invasive parameter that represented the degree of liver fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…In an attempt the histological study showed that lead can induce several alterations such as hypertrophy of hepatocytes, portal space and central vein dilatation, vacuolation and lymphocytic infiltration [11]. Meanwhile chronic exposure to lead imposes a potent toxic effect on liver cells manifested as glycogen depletion, cellular infiltration and liver architecture in the form of initiation of periportal fibrosis that may progress to liver cirrhosis [12]. Furthermore it has been suggested that mice were treated with lead acetate (10 mg/kg) dissolved in 0.02 ml of distill water decreased in cortical thickness of kidney significantly [13].…”
Section: Literature Reviewmentioning
confidence: 99%